2012
DOI: 10.2466/07.17.pms.114.2.397-406
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Disability and Elderly Stereotype in Motor Performance: Similar or Specific Effects?

Abstract: In three experimental studies, the effects of priming participants with the disability stereotype were investigated with respect to their subsequent motor performance. Also explored were effects of activating two similar stereotypes, persons with a disability and elderly people. In Study 1, participants were primed with the disability stereotype versus with a neutral prime, and then asked to perform on a motor coordination task. In Studies 2 and 3, a third condition was introduced: priming participants with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…Some priming paradigms mixed primes with distractor words (e.g., 15 out of 30 words in Bargh et al, 1996; seven out of 13 words in Bargh et al, 2001), whereas others presented only prime words (e.g., Chartrand & Bargh, 1996; McCulloch et al, 2008). Finally, studies have widely differed on their selection of behavioral measures, including performance measures (e.g., anagrams, word searches; Bargh et al, 2001; Crusius & Mussweiler, 2012), categorical choices of behavior or products (e.g., Albarracin, Wang, & Leeper, 2009; Sela & Shiv, 2009; Strahan et al, 2002), rates of helping or donation behavior (e.g., Macrae & Johnston, 1998; Smeesters, Wheeler, & Kay, 2009), and motor behaviors (e.g., time spent, number of pegs dropped during a manual dexterity task, the 9-hole peg test; Mathiowetz et al, 1985; Ginsberg, Rohmer, & Louvet, 2012; Wryobeck & Chen, 2003), among others. These factors were considered in an exploratory fashion, as a way of providing information on the future design of behavior priming studies.…”
Section: The Present Meta-analysismentioning
confidence: 99%
“…Some priming paradigms mixed primes with distractor words (e.g., 15 out of 30 words in Bargh et al, 1996; seven out of 13 words in Bargh et al, 2001), whereas others presented only prime words (e.g., Chartrand & Bargh, 1996; McCulloch et al, 2008). Finally, studies have widely differed on their selection of behavioral measures, including performance measures (e.g., anagrams, word searches; Bargh et al, 2001; Crusius & Mussweiler, 2012), categorical choices of behavior or products (e.g., Albarracin, Wang, & Leeper, 2009; Sela & Shiv, 2009; Strahan et al, 2002), rates of helping or donation behavior (e.g., Macrae & Johnston, 1998; Smeesters, Wheeler, & Kay, 2009), and motor behaviors (e.g., time spent, number of pegs dropped during a manual dexterity task, the 9-hole peg test; Mathiowetz et al, 1985; Ginsberg, Rohmer, & Louvet, 2012; Wryobeck & Chen, 2003), among others. These factors were considered in an exploratory fashion, as a way of providing information on the future design of behavior priming studies.…”
Section: The Present Meta-analysismentioning
confidence: 99%
“…Based on the assumption that simulating impairment activates beliefs about disability, we predicted that the behaviors of participants enrolled in simulations would be consistent with their beliefs about people with disabilities. Previous studies found that priming disability decreased the performance speed and manual dexterity of students without any disability (Ginsberg et al, ). In the same vein, simulating blindness caused participants to judge blind individuals as less successful and less autonomous than those in the no simulation condition (Silverman, Gwinn, & Van Boven, ).…”
Section: General Discussion and Conclusionmentioning
confidence: 88%
“…To conclude, the mere simulation of disability (i.e., no actual impairment) increased participants’ motivation and led them to be slower and more persevering, characteristics that echo stereotypical beliefs about disability (Ginsberg et al, ). Importantly, those results extended those of Study 1, in that here participants were led to simulate a disability without being actually impaired.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations